Der Monat des geringsten Niederschlags in Europa - Landmann, Wolfgang; Fezer, Fritz (ERDKUNDE, 1978)
The annual course of precipitation defines the western coasts of Europe as areas with maxima in winter, the minimum occurring in the Mediterranean climate in July/August, the Atlantic one doing so in April/May/June. There is a very gradual couvergence of the two, though it is only in S.W.France that their pure form extends further than 100km inland; it extends less far on steep mountainous coasts and occasionally further on the gently rising slopes of high mountains ranges. In the continental pattern of precipitation March-April receives least and May-August (according to latitude) most precipitation. In the transitional area between summer and winter maxima the period of precipitation is divided into spring and autumn rains. In continuation of the areas with winter rains there are those whose main minimum, though occurring in winter, is balanced by another one in summer, that resembles the adjacent type. In the lowland the west-east change of forms is so gradual that even the trained observer will scarcely notice it when travelling. The transitional region could be subdivided by the establishment of the frequency of certain minimum factors at the areal limits of important plants. Many large towns are continental islands, not only in respect of temperature but also with regard to their precipitation pattern. On the other hand, many mountains show island-like oceanic patterns of precipitation. In W. Landmann’s paper (1975) the primary and secondary precipitation minima of the whole of Europe are represented.